Translation to Serbian, cultural adaptation, reliability testing and validation of the questionnaire estimating the fear of injections - Aleksic, Dejan Z; Milosavljevic, Milos N; Bukonjic, Andriana M; Milovanovic, Jasmina R; Protrka, Zoran M; Radonjic, Vesela B; Jankovic, Slobodan M; Stefanovic, Srdjan M (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. The two-part questionnaire called Injection Phobia Scale (IPS)-Anxiety and IPS-Avoidance represents one of the most commonly used questionnaires for assessing the fear of injections. The aim of the present study was to translate and culturally adapt this questionnaire from English into Serbian as well as to assess reliability and validity of the translation. Methods. The translation and cultural adaptation of the IPS–Anxiety and IPS–Avoidance was performed in accordance with the International Society for Pharmacoeconomics and Outcomes Research (ISPOR) guidelines. Reliability testing, factor analysis and validation of Serbian translation of IPS-Anxiety and IPS-Avoidance were carried out on a sample of 485 students of pharmacy, or medicine at the University of Kragujevac, Serbia. Results. Serbian translation of IPS-Anxiety and IPS-Avoidance demonstrated high internal consistency with Cronbach’s alpha of 0.934 for IPS-Anxiety and 0.911 for IPS-Avoidance. Factor analysis of IPS-Anxiety showed that there are two domains, which we have called as Direct Experience (9 items) and Indirect Experience (9 items); factor analysis of IPS-Avoidance also pointed out on two domains referring to direct and indirect fear of injections. Female students scored higher on the scale showing more extensive injection phobia than male students. It is also interesting that students of pharmacy have higher level of injection phobia than students of medicine, and those students of the fifth year of study feel more fear of injections than students from the first four years. Conclusion. Serbian translation of IPS-Anxiety and IPS-Avoidance showed good psychometric properties on population consisted of students medicine and pharmacy.
Keywords: fear; injections; surveys and questionnaires; translating; serbia